Paraquat and maneb co-exposure induces noradrenergic locus coeruleus neurodegeneration through NADPH oxidase-mediated microglial activation. (1st April 2017) - Hou, Liyan; Zhang, Cong; Wang, Ke; Liu, Xiaofang; Wang, Hongwei; Che, Yuning; Sun, Fuqiang; Zhou, Xueying; Zhao, Xiulan; Wang, Qingshan
Highlights: Microglial activation induced by paraquat and maneb precedes noradrenergic neurodegeneration in locus coeruleus. NADPH oxidase activation contributes to microglia-mediated neuroinflammation and related noradrenergic neurodegeneration. Inhibition of NADPH oxidase by apocynin protects noradrenergic neurons against paraquat and maneb-induced toxicity. Abstract: Co-exposure to paraquat (PQ) and maneb (Mb) has been shown to increase the risk of Parkinson's disease (PD) and dopaminergic (DA) neurodegeneration in the substantia nigra pars compacta (SNpc) is observed in PQ and Mb-treated experimental animals. The loss of noradrenergic locus coeruleus (LC/NE) neurons in brainstem is a common feature shared by multiple neurodegenerative diseases, including PD. However, whether PQ and Mb is able to damage LC/NE neurons remains undefined. In this study, mice treated with combined PQ and Mb displayed progressive LC/NE neurodegeneration. Time course studies revealed that the activation of microglia preceded LC/NE neurodegeneration. Mechanistically, the activation of NADPH oxidase contributed to microglial activation and subsequent LC/NE neurodegeneration. We found that PQ and Mb co-exposure induced activation of NADPH oxidase as shown by increased superoxide production and membrane translocation of p47 phox, a cytosolic subunit of NADPH oxidase. Inhibition of NADPH oxidase by apocynin, a widely used NADPH oxidase inhibitor, suppressed microglial activation and gene expressions of proinflammatory factors. Furthermore, reduced activation of nuclear factor-κB (NF-κB) pathway was observed in apocynin-treated mice. More importantly, inhibition of NADPH oxidase by apocynin afforded LC/NE neuroprotection against PQ and Mb-induced neurotoxicity. Thus, our findings revealed the critical role NADPH oxidase-mediated microglial activation in driving LC/NE neurodegeneration induced by PQ and Mb, providing new insights into the pathogenesis of environmental toxins-induced PD.